Návrh marketingové strategie - Drápal, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá marketingovou strategií specifické společnosti. Práce obsahuje analýzu současné marketingové strategie. Na základě této analýzy jsou vypracovány návrhy a doporučení, které přispějí k vyššímu prodeji produktů, k vyššímu podílu na trhu a k vyšším ziskům firmy.

This thesis is focused on marketing strategy of a specific company. Thesis includes analysis of current marketing strategy. On the basis of the analysis are made suggestions and recommendations, which will lead to higher sales, higher market share and higher profit of analyzed company.
Marketing Strategy of a Company
Keywords: Marketing; marketingová strategie; marketingový mix; SWOT analýza; Marketing; marketing strategy; marketing mix; SWOT analysis